Mechanical strength study of expanded cork for the development of a surfboard - Correia, José Miguel Dias (2021)
Ecofriendly standards for mass products are a crucial necessity nowadays. Based on global needs for sustainable developments and the 2030 United Nations agenda, nding new sustainable materials that can replace oil-based ones and accomplishing the desired product properties are a necessity. This dissertation focused in enhancing the performance of expanded cork, and conferring to it more added value. To do it, a series of mechanical tests were carried out and a case-study was performed for an application for this material. To evaluate the mechanical properties and to determine the behaviour when used in di erent environments, uniaxial compression tests on blends of white and black cork agglomerates and 3 point bending of sandwich structure composites were performed. It was found out that this material as a granulate has low potential for energy absorption, but when allied with other materials could be a good solution for weight reduction while structural integriti. For sandwich structures, expanded cork works well when sandwiched between wood and polyester resin glass ber, being able to hold a large amount of energy and, at the same time, reduce weight and the environmental footstep impact of the composite. Related to this application was also studied the response of natural ax bers, that despite of being weaker, are still strong enough for many applications as for surfboard external skin lamination. The possible application of expanded cork on surfboard manufacturing was evaluated based on the previous results. A 3D virtual model, with the determined properties of the materials was used to simulate some experimental conditions. With the model was possible to validate the full prototype structure. The results indicate that, even at the expense of a slight increase in the overall weight, all mechanical needs were achieved when allied with other materials. Besides structural and technical performance evaluation, it is stated on this study that the use of expanded cork as a core material can further reduce environmental impact of surfboard in 62.8%. This outstanding result is the main motivation for further developments and works within this material.